Analysis of Community-based Organizations in Village Economic Development in Barru Regency - Syahrir, ‎; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
One of the government’s efforts in building and developing the village economy is by providing autonomy rights to manage the potential and resources they have independently through community-based organizations such as Village-Owned Enterprises (BUMDes). This study aims to analyze the role of community-based organizations in developing the village economy in Barru Regency, using a qualitative descriptive approach with secondary data analysis method. The results indicate that BUMDes has a significant influence in developing the village economy, one of the indicators of which is the Village Development Index (IDM) value. However, the condition of BUMDes in Barru Regency has not been able to significantly contribute in developing the village economy. Only a few BUMDes have shown a positive trend in their development, while a number of other BUMDes organizations are experiencing stagnant conditions with various problems. This is proven in the results of the analysis of the annual report where out of 40 BUMDes in Barru Regency, only about 52% of BUMDes have active management, 35% are less active, and 13% are not active. Some of the challenges faced are the ability of human resources (HR) of management, determination of the type and business unit to be managed, the ability of the management to identify the local potential of the village that has not been maximized, the limited number of accompanying experts, which is the mechanism of supervision and budget support. Strategies that can be carried out are the need to increase the number of experts/assistants, increase the HR in administration in identifying the local potential of the village through training and mentoring, revitalization of administrators who are not/less active, diversification of businesses according to the potential and needs of the local community, collaboration with the private sector, optimization of supervisory tasks through monitoring, evaluation and periodic accountability reports. Some of the challenges faced in managing BUMDes are the abilities of the HR administrators, determining the types and business units to be managed, the suboptimal utilization of local village potential, and monitoring mechanisms and budget support. Strategies that can be taken to overcome these challenges are the need for expert assistance in conducting business and risk analysis, business diversification according to community needs, collaboration with the private sector, coaching and training for administrators, and optimization of supervisory tasks through monitoring, evaluation, and periodic accountability reports.